POTENTIAL HARMS OF THE USE OF PROTON PUMP INHIBITORS: DEBATABLE PROBLEMS - Yu. V. Muravyev; O. R. Bobkova (Научно-практическая ревматология)
The paper discusses data on the high frequency of non-indicated use of proton pump inhibitors and on the manifestations of potential harms of their use.